2011
DOI: 10.1155/2011/589185
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Nitro and Chlorophenols Using Doped and Undoped Titanium Dioxide Nanoparticles

Abstract: Pure and Ag-TiO2nanoparticles were synthesized, with the metallic doping being done using the Liquid Impregnation (LI) method. The resulting nanoparticles were characterized by analytical methods such as scanning electron micrographs (SEMs), Energy Dispersive Spectroscopy (EDS), and X-ray diffraction (XRD). XRD analysis indicated that the crystallite size ofTiO2was 27 nm to 42 nm while the crystallite size of Ag-TiO2was 11.27 nm to 42.52 nm. The photocatalytic activity of pureTiO2and silver dopedTiO2was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…The aggregation amplified with increasing the concentration of Ag loading from 0.5 g to 1.4 g, as confirmed by EDX analysis. The aggregation is more prominent in the P-4 (1.4 g Ag@TiO 2 ) sample, and this may tremendously reduce the band gap of TiO 2 and consequently improved photocatalytic removal efficiency [23]. The EDX analysis of P-4 (Figure 2) demonstrated that Ag is not uniformly dispersed on the surface of TiO 2 , which is in accordance with previous works [24,25].…”
Section: Resultssupporting
confidence: 88%
“…The aggregation amplified with increasing the concentration of Ag loading from 0.5 g to 1.4 g, as confirmed by EDX analysis. The aggregation is more prominent in the P-4 (1.4 g Ag@TiO 2 ) sample, and this may tremendously reduce the band gap of TiO 2 and consequently improved photocatalytic removal efficiency [23]. The EDX analysis of P-4 (Figure 2) demonstrated that Ag is not uniformly dispersed on the surface of TiO 2 , which is in accordance with previous works [24,25].…”
Section: Resultssupporting
confidence: 88%
“…As imagens obtidas por MEV evidenciam aglomerados de escala micrométrica e pequenas partículas pontuais na escala nanométrica, conforme observado na Figura 2. De acordo com Ilyas et al, (2011), infere-se que os pequenos pontos esféricos isolados na Figura 2-b são nanopartículas de TiO2, e as partículas em formato filamentoso correspondem à prata. Conforme mostra a Figura 3, a análise do EDS reafirma a composição do nanocompósito, uma vez que titânio, oxigênio e prata estão presentes com uma porcentagem mássica coerente, em relação às massas de AgNO3 e TiO2 utilizadas no processo de dopagem.…”
Section: Caracterização Por Mev/edsunclassified
“…WanJum et al reported enhanced photodegradation of Cu-porphyrin modified TiO 2 (13.9 ppm of p-nitrophenol in 66 mins) [39]. Ilyas et al have reported better catalytic activity for the degradation of p-nitrophenol (4 ppm) using Ag-doped TiO 2 under UV irradiation (98%) compared to that of pure TiO 2 (83%) in 1 h [40]. Photodegradation using surface modified TiO 2 with salicylic acid resulted in 91.1% of degradation of 1 ppm of p-nitrophenol in 180 mins [28].…”
Section: Photodegradation Of P-nitrophenolmentioning
confidence: 99%